2012
DOI: 10.1016/j.ydbio.2011.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Sphingosine-1-phosphate signaling mutants reveals endodermal requirements for the growth but not dorsoventral patterning of jaw skeletal precursors

Abstract: Development of the head skeleton involves reciprocal interactions between cranial neural crest cells (CNCCs) and the surrounding pharyngeal endoderm and ectoderm. Whereas elegant experiments in avians have shown a prominent role for the endoderm in facial skeleton development, the relative functions of the endoderm in growth versus regional identity of skeletal precursors have remained unclear. Here we describe novel craniofacial defects in zebrafish harboring mutations in the Sphingosine-1-phospate (S1P) type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 43 publications
9
54
1
Order By: Relevance
“…putative hypomorphic allele of smad5, we have shown that reduced Bmp signaling causes viscerocranial defects similar to those observed in some endoderm mutants (Swartz et al, 2011;Choe and Crump, 2014). Bmp signaling has been implicated in endoderm specification (Tiso et al, 2002), which is crucial for proper formation of the craniofacial skeleton (Balczerski et al, 2012;Couly et al, 2002;David et al, 2002). Data from a Bmp response element (BRE; derived from the X. laevis vent2 promoter) transgenic zebrafish line demonstrate that the endoderm receives Bmp signaling during pharyngeal arch development .…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…putative hypomorphic allele of smad5, we have shown that reduced Bmp signaling causes viscerocranial defects similar to those observed in some endoderm mutants (Swartz et al, 2011;Choe and Crump, 2014). Bmp signaling has been implicated in endoderm specification (Tiso et al, 2002), which is crucial for proper formation of the craniofacial skeleton (Balczerski et al, 2012;Couly et al, 2002;David et al, 2002). Data from a Bmp response element (BRE; derived from the X. laevis vent2 promoter) transgenic zebrafish line demonstrate that the endoderm receives Bmp signaling during pharyngeal arch development .…”
Section: Introductionsupporting
confidence: 56%
“…Mutants with disrupted endoderm morphogenesis exhibit defects to the viscerocranium (Balczerski et al, 2012;Choe et al, 2013;Choe and Crump, 2014) that are reminiscent of the phenotypes in Dorsomorphin-treated embryos. To determine if Bmp signaling mediates endoderm development, we treated sox17:dsRed transgenic embryos with Dorsomorphin and imaged the pharyngeal arches at 36 hpf.…”
Section: Proper Endoderm Morphology Requires Bmp Signalingmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, a recent study indicates that S1pr2 signaling in the endoderm is crucial for jaw development in zebrafish (Balczerski et al, 2012), further supporting the roles of this signaling pathway in endoderm development.…”
Section: Research Article Development 140 (4)mentioning
confidence: 72%
“…We hypothesize that mandibular growth is regulated by a similar signaling feedback loop. Shh expression in the pharyngeal endoderm is essential for mandibular development, where it directs neural crest survival and outgrowth (Ahlgren and Bronner-Fraser, 1999;Balczerski et al, 2012;Brito et al, 2006;Brito et al, 2008;David et al, 2002;Jeong et al, 2004;Veitch et al, 1999). Exogenous Shh, when placed in the mandibular arch environment, activates Bmp4 and Fgf8 expression in the oral ectoderm, resulting in the development of supernumerary mandibles (Brito et al, 2008).…”
Section: Regulative Development Of the Mandiblementioning
confidence: 99%